Identification of a new genetic variant (G231N, E232T, N235D) of peptidylarginine deiminase from P. gingivalis in advanced periodontitis - Bereta, Grzegorz P.; Strzelec, Karolina; Łazarz-Bartyzel, Katarzyna; Dziedzic-Kowalska, Agata; Nowakowska, Zuzanna; Krutyhołowa, Anna; Bielecka, Ewa; Kantyka, Tomasz; Grabiec, Aleksander M.; Kaczmarzyk, Tomasz; Chomyszyn-Gajewska, Maria; Potempa, Jan; et al. (Frontiers in Immunology, 2024)
Chronic periodontitis (CP), an inflammatory disease of periodontal tissues driven by a dysbiotic subgingival bacterial biofilm, is also associated with several systemic diseases, including rheumatoid arthritis (RA).Porphyromonas gingivalis, one of the bacterial species implicated in CP as a keystone pathogen produces peptidyl arginine deiminase (PPAD) that citrullinates C-terminal arginine residues in proteins and peptides.Autoimmunity to citrullinated epitopes is crucial in RA, hence PPAD activity is considered a possible mechanistic link between CP and RA. Here we determined the PPAD enzymatic activity produced by clinical isolates of P. gingivalis, sequenced the ppad gene, and correlated the results with clinical determinants of CP in patients from whom the bacteria were isolated. The analysis revealed variations in PPAD activity and genetic diversity of the ppad gene in clinical P. gingivalis isolates. Interestingly, the severity of CP was correlated with a higher level of PPAD activity that was associated with the presence of a triple mutation (G231N, E232T, N235D) in PPAD in comparison to W83 and ATCC 33277 type strains. The relation between mutations and enhanced activity was verified by directed mutagenesis which showed that all three amino acid residue substitutions must be introduced into PPAD expressed by the type strains to obtain the super-active enzyme.Cumulatively, these results may lead to the development of novel prognostic tools to assess the progress of CP in the context of associated RA by analysing the ppad genotype in CP patients infected with P. gingivalis.